Local Flap Technique for Soft Tissue Defect in Compound Leg Injuries: A Reliable Single Stage Coverage - Sadh, Raghvendra; Pal, Vishnu (Medicine and Medical Research: New Perspectives Vol. 11, 2024)
Objective: The aim of this study is to evaluate the feasibility of local flaps, Fasciocutaneous, Muscle & Musculocutaneous flaps, in the management of soft tissue defects with exposed fracture bone fragments in compound injuries of the lower extremity as a single-stage procedure (particularly the leg). To lay down clear and concise guidelines, merits and demerits of this technique for Orthopaedic surgeons in trauma wards. Methods: In traumatised lower extremity having a soft tissue defect & an exposed bone with or without associated fractures. Local flaps provide a reliable single-stage procedure for coverage of lower extremity soft tissue defects. The traumatised limb selected in which the wound was found to be preferably in the upper 1/3rd, middle 1/3rd& uppermost part of the lower 1/3rd leg due to easy accessibility & placement of the local flap to these areas. All flaps i.e. Fasciocutaneous, Musculocutaneous & local muscle flaps were undertaken as a delayed procedure after careful evaluation of traumatised limb by repeated dressings, debridement & control of infection. Daily assessment of the wound for infection, and motor & sensory & vascular status was made. Definitive wound coverage was done by using a selected technique in a routine operation at the same time a split-thickness skin graft was applied on muscle pedicle flap or the defective area created by the transposition of Fasciocutaneous, Musculocutaneous flap. Fixation of bone was done before applying the technique. Results: Stable wound coverage was achieved in all patients. The excellent result was obtained in Muscle & Musculocutaneous flaps while the good result was obtained in 10% of cases of Fasciocutaneous flaps. In a study longest duration follow-up was 14 months & shortest was 3 months. 20 cases of traumatised lower extremities (particularly the leg) which required local flap coverage for soft tissue defects with exposed bone fragments. Conclusion: Stable coverage can be achieved by flap techniques using Fasciocutaneous, Muscle or Musculocutaneous flaps. Coverage of exposed cortical bones, tendons & major vessels & adequate control of infection can be achieved by Muscle & Musculocutaneous flap in post traumatised limb. Fasciocutaneous flap (Ponten super flap) is very useful in the repair of soft tissue defects as it is a much simpler, easy to design & construct large flaps are safe due to good circulations, require less time without any functional loss, post-operative management is simple for both patient & staff.